PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SUPLIER BAHAN BAKU DENGAN METODE AHP (Analitycal Hierarchy Process) - Ferry Irmawan; Fitri Marissa (IIB Darmajaya, 2018)
This research was conducted because of the problem of the limitations of the media used in the process of selecting raw material suppliers at PT. Mayatama Manungal Sentosa, Malang. This study aims to design a decision support system that is able to help the company's performance in determining suppliers of raw materials using the AHP (Analytical Hierarchy Process) method. The Analytical Hierarchy Process (AHP) method is a method used in designing a decision support system. The concept used by the AHP method is to change qualitative values into quantitative values. So that the decisions taken can be more objective. The results of the research are application systems that have been tested and stated to meet the expected objectives. Based on the AHP method test can be produced the following score MANUFACTURER-A, which is 0.437462933, then PRODUCER-B is 0.285721883, and PRODUCER-C is 0.279084967.Keywords : Analytical Hierarchy Process (AHP) Method